LARANGAN JUAL BELI TANAH SOKO SEBAGAI ‘URF ṢAḤĪḤ DIALEKTIKA HUKUM ADAT DAN HUKUM ISLAM DI KAMPAR - Zikri Assidiqqi (Institut Agama Islam Ngawi, 2026)
This study examines the customary prohibition on selling Tanah Soko in Kualu Village, Kampar, Riau, and analyzes its conformity with Islamic law. This qualitative field study used a normative Islamic-law approach and collected data through semi-structured interviews with six purposively selected informants, consisting of ninik mamak and community members involved in Tanah Soko management. Data were validated through source, method, and theoretical triangulation. The findings show that Tanah Soko is divided into Soko Tinggi, communal ancestral land that cannot be alienated, and Soko Rendah, individual inherited land that may be transferred. The prohibition on selling Soko Tinggi is enforced through multilevel customary deliberation. In Islamic law, the prohibition is valid because individuals do not possess full ownership (al-milk al-tām), while the custom meets the criteria of ʿurf ṣaḥīḥ and maṣlaḥah mursalah. Thus, the prohibition demonstrates harmonious integration between customary law and Islamic law.